Comparative analysis of adverse event risks in breast cancer patients receiving pembrolizumab combined with paclitaxel versus paclitaxel monotherapy: insights from the FAERS database - Li, Yilun; Yang, Xiaolu; Ma, Li (Frontiers in Pharmacology, 2024)
Objective This study aimed to evaluate the risk of adverse events (AEs) in breast cancer patients treated with pembrolizumab combined with paclitaxel versus those receiving pembrolizumab or paclitaxel monotherapy, using the FDA Adverse Event Reporting System (FAERS) database. Methods Data were extracted from the FAERS database for breast cancer patients treated with pembrolizumab combined with paclitaxel or with pembrolizumab or paclitaxel monotherapy from Q1 2016 to Q2 2023. Disproportionation analysis was performed by calculating the reporting odds ratio (ROR) with corresponding 95% confidence interval (95% CI), the information component (IC), and the lower bound of the information component 95% confidence interval (IC025) to identify potential safety signals. Results No significant difference in AEs was observed between the combined treatment group and the pembrolizumab monotherapy group. However, the combined treatment group exhibited a substantial increase in AE risk compared to the paclitaxel monotherapy group. The most significant increases in AE risk were adrenal insufficiency (ROR = 189.94, 95% CI 25.41–1419.7, IC = 3.37, IC025 = 1.59), hypophysitis (ROR = 99.46, 95% CI 12.72–777.4, IC = 3.31, IC025 = 1.44), and myocarditis (ROR = 69.5, 95% CI 8.55–565.23, IC = 3.25, IC025 = 1.33). The time-to-event for combined treatment was 35 (34–70) days, for pembrolizumab was 43 (35–90) days, and for paclitaxel was 42 (37–76) days. The combination therapy group demonstrated significantly shorter intervals to the onset of adrenal insufficiency (p = 0.008), myocarditis (p < 0.001), and immune-related enterocolitis (p = 0.009). Conclusion Analysis of the FAERS database indicates that combination therapy significantly elevates the risk of adrenal insufficiency, myocarditis, hypophysitis, and immune-related enterocolitis compared to paclitaxel monotherapy. These findings provide critical insights for clinicians in predicting and managing potential AEs associated with this treatment regimen.